Estrategias promocionales en las ventas en la Empresa “Rico Pan” del cantón Babahoyo provincia de Los Ríos en el periodo 2023. - Cerezo Aguiño, Damaris Noemi (2024)
This project analyzes the promotional strategies used by the company Rico Pan in the canton of Babahoyo, province of Los Ríos, during the year 2023, with the aim of increasing sales and improving brand presence in the local market. The research focuses on examining the promotional strategies employed by Rico Pan in the city of Babahoyo. To conduct this analysis, a significant method was used: the hypothetico-deductive method. The phase involved observation during the information gathering of the SWOT matrix and surveys conducted with the company's customers. The results indicate that direct promotions, such as discounts, special offers, and promotions, are absent within the company, which leads to a decrease in product sales. Additionally, it was observed that participation in community events and local fairs has not increased brand visibility. Based on these findings, it is recommended to continue implementing promotional strategies and explore new digital opportunities to further strengthen the promotional strategy.